h - Chiu, Dickson K. W.; Wang, Minhong; Popescu, Elvira; Li, Qing.; Lau, Rynson; Shih, Timothy K.; Yang, Chu-Sing.; Sampson, Demetrios G.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the Workshops held at the ICWL 2013 International Conference on Web Based Learning in Kenting, Taiwan, in October 2013. The 29 papers presented were carefully reviewed and selected for inclusion in this volume. They were held at the following workshops: First International Workshop on Ubiquitous Social Learning, USL 2013; 2013 International Workshop on Smart Living and Learning, IWSLL 2013; Third International Symposium on Knowledge Management and e-Learning, KMEL 2013; 2013 International Workshop on Cloud Computing for Web-Based Learning, IWCL 2013; 2013 International Workshop on Web Intelligence and Learning; WIL 2013; and the 2013 International Workshop on e-book and Education Cloud, IWEEC 2013.
International Workshop on Web Intelligence and Learning -- A Web-Based Virtual Lab Platform for Algorithm Learning -- A Genetic Algorithm-Based Multiple Characteristics Grouping Strategy for Collaborative Learning -- Adaptation Based on Navigation Type and Learning Style -- A Novel Recommendation Relevancy Measure for Collaborative Filtering -- Automatic Clustering of Research Articles Using Domain Ontology and Fuzzy Logic -- Model of Teachers$1 (BPersonalized Decision Making on Activities and Resources in Web-Based Training -- International Symposium on Knowledge Management and E-Learning Analyzing Learning Flows in Digital Learning Ecosystems -- Research Trends of Language Learning in Virtual Reality from 2003 to 2012: A Content Analysis -- International Workshop on Ubiquitous Social Learning An Interactive 3D Social Graphs for Social Learning -- Improving KeyNote Trust Management Model Based on User Behavior for Social Learning -- International Workshop on E-Book and Education Cloud -- Enhancing Teamwork Performance in Mobile Cloud-Based Learning -- An E-Book Based Competitive Learning System for Conducting Mobile Plants Learning Activities to Improving Student Learning Outcome -- The E-Book Learning System with Problem-Based Learning in a Public Health Nursing Practice Course -- Increasing Students$1 (BVocabulary Size Through the Use of Latent Semantic Analysis in a Mobile Learning Environment -- Analyzing Immersion in Digital Game-Based E-Book Learning Through Learners$1 (BFacial Expressions -- International Workshop on Cloud Computing for Web-Based Learning The Learning Effect of Students$1 (BCognitive Styles in Using Cloud Technology -- Framework of Supporting Structured Game Script Learning System -- Performance Analysis Using Petri Net Based MapReduce Model in Heterogeneous Clusters -- Integration of MapReduce with an Interactive Boosting Mechanism for Image Background Subtraction in Cultural Sightseeing -- An Weighted-Content Strategy for Integrating Heterogeneous Itembanks -- Teaching Effectively with the Multi-screen Multimedia Integrated System -- International Workshop on Smart Living and Learning -- Preliminary Investigation of Interactive Behaviors in Distant Collaborative Exergame -- Second Heart Sound (S2) Decomposition by Hilbert Vibration Decomposition (HVD) for Affective Signal Modeling and Learning -- Clustering XML Documents for Web Based Learning -- Cultural Sensitivity Training Task: An Avenue of Enhancing Students$1 (BCultural Awareness and Its Perspectives of Web-Based Learning -- Web-Based-Learning via Tajen Cloud -- Complementary to Web-Based Education on Summer Camp of Marine Energy -- Web-Based Ubiquitous Learning -- A Virtual Reality Based Training System for Cultural Tourism.s
Keywords: Computer science; Information storage and retrieval; User interfaces (Computer systems).; Artificial intelligence; Education -- Data processing; Computer Science; Computers and Education; User Interfaces and Human Computer Interaction; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Electronic books